Efektivitas dan Dampak Program SIMANTRI Terhadap Pendapatan dan Kesempatan Kerja Rumah Tangga Petani di Desa Kelating Kecamatan Kerambitan Kabupaten Tabanan - Wibawa, I Ketut Trisna; Yasa, I Nyoman Mahaendra (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2013)
To accelerate the growth and development of agriculture in the rural area and at the same time reducing the poverty and unemployment in the rural area, the government launched the Integrated Agricultural System Program (SIMANTRI), where the SIMANTRI program is an breakthrough effort in accelerating agricultural technology adoption which is the improvement of pilot project in accelerating technology transfer to the rural community for the purpose to improve the income and work opportunity of farmer’s household. The research entitled “The Effectiveness and the Impact of SIMANTRI Program to the Income and Work Opportunity of Farmer’s Household at Kelating Village Sub-district of Kerambitan Regency of Tabanan” aims to measure the level of effectiveness and impact of SIMANTRI program to the income and work opportunity of farmer’s household at Kelating Village Sub-district of Kerambitan Regency of Tabanan. Analysis tool used in this research is descriptive statistical to find out the program effectiveness and non-parametric differential test statistical analysis to find out SIMANTRI program impact to the income and work opportunity of farmer’s household at Kelating Village Sub-district of Kerambitan Regency of Tabanan. Analysis result shows that SIMANTRI program effectiveness at 98.94% means effectiveness level of the Integrated Agricultural System Program (SIMANTRI) is very effective. Analysis result also shows that SIMANTRI program has positive and significant impact to the income and work opportunity of farmer’s household at Kelating Village Sub-district of Kerambitan Regency of Tabanan.
Keywords: Effectiveness; Simantri; Income; Work opportunity